What proportion of patients with bone and soft tissue tumors contracted coronavirus-19 and died from surgical procedures during the initial period of the COVID-19 pandemic? results from the multicenter British Orthopaedic Oncology Society Observational Study - Rajasekaran, RB; Ashford, RU; Cosker, TDA; Stevenson, JD; Jeys, L; Pollock, R; Rankin, KS; Cool, P; Patton, JT; Whitwell, D; Gibbons, CLMH; Carr, A; et al. (Lippincott, Williams & Wilkins, 2020)
Background: Delivering uninterrupted cancer treatment to patients with musculoskeletal tumors has been essential during the rapidly evolving coronavirus 2019 (COVID-19) pandemic, as delays in management can be detrimental. Currently, the risk of contracting COVID-19 in hospitals when admitted for surgery and the susceptibility due to adjuvant therapies and associated mortality due to COVID-19 is unknown, but knowledge of these potential risks would help treating clinicians provide appropriate cancer care.